Mechanism Of Spiral Potato Crips Machine For Increasing MSMEs Production Capacity In Mojokerto - Muzaki, Iqbal; Subaderi, Subaderi; Wahju Rijanto, Ong Andre; Hariyanto, Krisnadhi; Dewi, Fitriya Gemala; Suwondo, Ampar Jaya (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2023)
Potatoes are Indonesia's abundant agricultural product. Potatoes can be used as a substitute for rice. Therefore potatoes are very popular as special food preparation in Indonesia. Geographically, Indonesia is an agricultural country. It greatly supports agricultural production. So that the quality and commodity of agricultural products (potatoes) remain high, it is necessary to have new ideas or ideas, one of which is processing potato chips to be of high quality. They prompted researchers to develop innovative equipment to speed up the process of processing potatoes into spiral chips by making appropriate technology machines that can produce more optimal production compared to conventional methods, namely 15 kg/hour. This appropriate technology machine is implemented in MSME potato chips in Kemiri Village, Pacet District, Mojokerto Regency. This machine can help speed up processing so that production time can be increased optimally.